Evaluation on the performance of magnesium phosphate cement-based engineered cementitious composites (MPC-ECC) with blended fly ash/silica fume. (25th July 2022) - Feng, Hu; Nie, Shuang; Guo, Aofei; Lv, Lijun; Yu, Jiahuan
Highlights: Fly ash (FA) and silica fume (SF) were blended with different proportions. Effect of blended FA/SF on the workability of the MPC-ECC was investigated. Effect of blended FA/SF on the micromechanical properties of MPC-ECC was explored. Effect of blended FA/SF on the macromechanical properties of MPC-ECC was explored. The suggested values of pseudo-strain hardening indices were given for MPC-ECC. Abstract: To develop magnesium phosphate cement-based engineered cementitious composites (MPC-ECC) that can be well used for rapid building repair, this study explores the influence of blended fly ash/silica fume on the compressive strength, direct tensile properties, and micromechanical properties of MPC-ECC. And the relationship between two pseudo strain-hardening indices ( PSHσ and PSHJ ) and ultimate tensile strain is established. The micromechanical analysis indicates that the blending of 30% fly ash and 10% silica fume significantly improves the fiber bridging capacity and fiber bridging complementary energy; however, the blended fly ash/silica fume reduces the tensile cracking strength, elastic modulus, and fracture toughness of the matrix. In addition, the blended fly ash/silica fume increases the compressive strength, up to 41.67 MPa, and also improves the tensile properties of MPC-ECC. The strain hardening behavior is more improved as the fly ash/silica fume content increases. Besides, the ultimate tensile strain and the pseudo-strain hardening indices are positively correlated, showing that the pseudo-strain hardening indices can be used to design MPC-ECC with specific ultimate tensile strains. To ensure that the MPC-ECC achieves an ultimate tensile strain of above 3%, PSHσ and PSHJ are recommended to reach 2.12 and 21.32, respectively, or more at the same time.